GENDER CHALLENGES AND DIVERSITY IN COMPENSATION MANAGEMENT: AN EMPIRICAL STUDY OF CONTEMPORARY ISSUES IN MODERN INDUSTRY - Suryana, Ega Sebe; Amalia, Dira Rizki; Muawanah, Siti; Mukhlis, Ahmad (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study explores the complex dynamics of gender and diversity challenges in compensation management in modern industries. This comprehensive study aims to analyse the structural mechanisms that influence compensation gaps, identify causal factors, and formulate transformative strategies to achieve equity. Through a multidisciplinary methodological approach, the study combines quantitative and qualitative analyses of academic literature and policy documents. Findings reveal that complex factors, including cultural bias, organisational structures, and limited opportunities, influence compensation gaps. The study offers a comprehensive theoretical framework to understand and address compensation inequity, emphasising the importance of multidimensional interventions. Recommendations include the development of gender-responsive audit mechanisms, inclusive capacity-building programs, and organisational culture transformation. The main contribution of this study is the systematic mapping of compensation equity challenges and the provision of a strategic blueprint for organisations and policymakers.